Manajemen Homeschooling dalam Pendidikan Islam: Analisis Kelebihan dan Kekurangan Implementasi - Resty Aulia Nurmaya Ulfi; Nabila Dewi Yulianti; Annisa Annisa; Ajahari Ajahari (Institut Agama Islam Hidayatullah Batam, 2026)
The management of boarding systems in Madrasah Aliyah (MA) Boarding The study aims to analyze homeschooling management from the perspective of Islamic education using the POAC framework and to identify the advantages and disadvantages of its implementation. The study employs an analytical literature review method using content analysis and thematic analysis of relevant journals and books. The results indicate that homeschooling offers advantages such as more intensive internalization of Islamic values, learning flexibility, a conducive environment, and strengthened parent-child relationships. However, homeschooling also has weaknesses, such as limited social interaction, dependence on parental competence, and high demands on time and resources. Therefore, structured management is required for Islamic homeschooling to run effectively.